Barbie-Cueing Weight Perception. (May 2019) - Saccone, Elizabeth J.; Chouinard, Philippe A.
It was previously reported that Barbie feels heavier than Ken when both dolls are matched for mass. However, we felt it was unclear from this earlier report if the effects went beyond a typical size-weight illusion. By providing better controls, we conclude more confidently that doll features other than size influence weight perception. Specifically, conceptual knowledge, in the form of culturally reinforced biases, seems to affect how we perceive their weight.